Metal ion induced nanocluster membrane material and preparation method thereof

By forming a metal ion-monomer coordination cluster structure on the membrane material, the problems of poor selectivity and insufficient water flux in the separation of organic matter and inorganic salts are solved, and efficient separation performance and water flux are achieved.

CN119588184AActive Publication Date: 2025-03-11JIAXING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510026635.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-11
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing membrane materials have poor selectivity and insufficient water flux in the separation of organic matter and inorganic salts, making it difficult to effectively control the interface structure and stability.

Method used

By pouring a solution containing polymer monomer and metal ion compound onto a polymer film, a metal ion-monomer coordination cluster structure is formed, and metal ion-induced nanocluster film material is prepared through interfacial polymerization reaction and thermal curing.

Benefits of technology

High selective separation performance and high water flux were achieved, specifically manifested as the retention rate of Congo red is not less than 90.57%, the retention rate of inorganic salt is not more than 10.82%, and the water flux can reach 496.31L m-2h-1bar-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588184A_ABST
    Figure CN119588184A_ABST
Patent Text Reader

Abstract

The invention relates to a metal ion-induced nanocluster membrane material and a preparation method thereof, and the preparation method comprises the following steps: pouring a solution containing a polymer monomer and a metal ion compound on one side surface of a polymeric membrane, soaking, depositing on the polymeric membrane to form a metal ion-monomer coordination cluster structure, and adding 1, 3, 4, 5, 6-tetramethyl-1, 3, 5-tetramethyl-1, 3, 5-tetramethyl-1, 3, 5-tetramethyl-1, 3, 5-tetramethyl-1, 3, 5-tetramethyl-1, pouring a 1, 3, 5-trimesoyl chloride solution on the surface of one side, where the metal ion-monomer coordination cluster structure is deposited, of the polymeric membrane, carrying out interfacial polymerization reaction, and carrying out thermocuring and water washing after the reaction to obtain a membrane material; the retention rate of the membrane material to Congo red is not lower than 90.57%, the retention rate of the membrane material to inorganic salt is not higher than 10.82%, and the water flux is 102.55-496.31 L m <-2 > h <-1 > bar <-1 >. During preparation, a nanocluster microstructure is constructed on the surface of the membrane, so that the transmission channel quantity of permeated water and ions is increased, and the selective interception and permeation flux of the membrane material are synchronously improved; the prepared membrane material has a good selective interception effect on Congo red and inorganic salt and is high in water flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane material preparation, and relates to a metal ion-induced nanocluster membrane material and a preparation method thereof. Background Art

[0002] As a highly efficient separation method, membrane separation technology has the characteristics of simple operation, energy saving, environmental protection, and environmental friendliness. Using membrane technology to separate organic matter and inorganic salts is a prerequisite and basis for purifying organic molecules (drugs, dyes, small peptides, etc.), recovering salts at a high value, and achieving zero wastewater discharge. However, the separation of organic matter and inorganic salts faces two difficulties: first, the size of small organic molecules and salt ions is similar, and the size screening mechanism is difficult to be completely effective; second, it is difficult to achieve a major breakthrough in membrane permeation flux while ensuring the separation of organic matter / salts. Therefore, the development of high-performance organic matter / salt separation membrane materials has become an important topic in the fields of membrane science, environment, and refining and purification.

[0003] To this end, researchers have carried out a series of work on the development of membrane materials for improving organic / salt selective separation and high water flux. In 2004, a loose nanofiltration membrane that can intercept organic matter and pass salt was obtained and used in water treatment processes for the first time (Reference 1: J. Environ. Manage. 2004, 73: 267-274). More and more studies have designed membrane materials from the perspectives of interface regulation, physicochemical regulation, and pore structure design to improve organic / salt separation performance (Reference 2: Chem. Eng. J., 2022, 450: 138057; Reference 3: Sep. Purif. Technol., 2022, 283: 120163; Reference 4: J. Mater. Chem. A, 2023, 11: 2367-2376), but the interface structure and stability of membrane materials are still difficult to control, which in turn affects the improvement of performance such as selective separation and water flux. How to prepare membrane materials with controllable structure and stable performance by regulating the interfacial polymerization mode and membrane surface microstructure morphology is a key issue that needs to be urgently solved in organic / salt membrane separation.

[0004] Therefore, it is of great significance to study a metal ion-induced nanocluster membrane material and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the prior art and to provide a metal ion-induced nanocluster membrane material and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a metal ion-induced nanocluster membrane material comprises the following steps: pouring a solution containing polymer monomers and metal ion compounds on one side of a polymer membrane, and depositing the solution on the polymer membrane after soaking to form a metal ion-monomer coordination cluster structure; pouring out the solution after the soaking, and washing it with deionized water to remove unreacted ions; and then pouring a 1,3,5-benzenetricarboxylic acid chloride solution on one side of the polymer membrane to deposit the metal ion-monomer coordination cluster structure, and performing an interfacial polymerization reaction; and performing heat curing and water washing after the reaction to obtain a metal ion-induced nanocluster membrane material.

[0008] The polymer monomer is a compound containing an amino group.

[0009] As the preferred technical solution:

[0010] In the method for preparing a membrane material of metal ion-induced nanoclusters as described above, the polymer membrane includes a base membrane and a support membrane, and the support membrane is formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane.

[0011] In the method for preparing a membrane material of metal ion-induced nanoclusters as described above, the base membrane is a polytetrafluoroethylene filter membrane, an organic nylon filter membrane, a polypropylene filter membrane or a polyvinylidene fluoride filter membrane.

[0012] The preparation method of the metal ion-induced nanocluster membrane material as described above has an effective area of ​​9.621 cm 2 The amount of polypyrrole-coated bacterial cellulose is 20 to 60 mg.

[0013] In the method for preparing a metal ion-induced nanocluster membrane material as described above, the polymer monomer is aniline, pyrrole or dopamine, and the metal ion compound is cobalt nitrate, zinc nitrate, iron nitrate, copper nitrate, cobalt chloride, zinc chloride, iron chloride or copper chloride.

[0014] As described above, in the method for preparing a membrane material of a metal ion-induced nanocluster, the solvent in the solution containing polymer monomers and metal ion compounds is a mixture of ethanol and water (the volume ratio of ethanol to water is 2:5); in the solution containing polymer monomers and metal ion compounds, the mass percentage concentration of the polymer monomers is 0.05-1.50%, and the concentration of the metal ions is 0.025-0.2M.

[0015] In the above-mentioned method for preparing a metal ion-induced nanocluster membrane material, the solution containing the polymer monomer and the metal ion compound further contains piperazine, and the mass percentage concentration of the piperazine does not exceed 0.50%.

[0016] In the method for preparing a metal ion-induced nanocluster membrane material as described above, the mass percentage concentration of the 1,3,5-benzenetricarboxylic acid chloride solution is 0.05-0.4%.

[0017] In the method for preparing a metal ion-induced nanocluster membrane material as described above, the thermal curing temperature is 50 to 70° C. and the thermal curing time is 10 to 20 minutes.

[0018] The present invention also provides a membrane material of metal ion-induced nanoclusters prepared by the method described in any one of the above items, wherein the interception rate of the membrane material of metal ion-induced nanoclusters for Congo red is not less than 90.57%, the interception rate for inorganic salts is not more than 10.82%, and the water flux is 102.55 to 496.31 L m-2h-1bar -1 .

[0019] The principle of the present invention is as follows:

[0020] Inspired by the coordination chemistry theory, taking metal-organic framework as an example, metal ions and organic ligands provide coordination connection to form porous materials with stable and adjustable (sub) nanopore structures. If metal ions are introduced into the aqueous phase system of interfacial polymerization, nanoclusters centered on metal ions are formed through coordination with organic small molecule monomers. While regulating the interfacial amide reaction, a membrane surface with a special morphological microstructure can be formed. The steric hindrance effect and the disorder of the molecular weight of polyamide can be used to form more nano transmission channels, thereby obtaining membrane materials with high water flux and selective separation performance to better meet the needs of organic / salt separation applications.

[0021] The present invention constructs a nanocluster microstructure on the functional layer of the membrane surface by coordinating metal ions with polymer monomers or metal ions with polymer monomers and piperazine. The structure is generated in situ during the preparation process, avoiding the problems of uneven dispersion and insufficient stability. Due to the formation of the nanocluster microstructure, the polyamide polymerization process and rate of the interface are changed. On the one hand, it is reflected in the change of the surface microstructure morphology. The stacking arrangement of the spherical structure of the nanoclusters makes the originally flat polyamide surface appear undulating. The undulating "peak and valley" structure formed is helpful for improving the water flow force and increasing the contact area between the membrane surface and water during the separation process, which are all conducive to improving selective separation and water flux. On the other hand, due to the presence of clusters, nano-defect pores are formed in the polyamide network. The formation of these pores is due to the steric hindrance generated when the metal ions are coordinated with the monomers or the interaction between the clusters, which leads to the instability of the local structure. These newly added nano-defect pores greatly reduce the mass transfer resistance of water / salt transmission and selectively block the dye, which is conducive to the selective separation of dyes / salts and rapid water flux. The water flux of the obtained membrane material can reach 496.31L m -2 h -1 bar -1The interception rate of Congo red is not less than 90.57%, and the interception rate of inorganic salts is not more than 10.82%, which effectively realizes the separation of organic dyes and inorganic salts. In addition, the preparation method of the membrane material is simple and easy to control, and has good prospects for large-scale preparation and application.

[0022] Beneficial effects:

[0023] (1) A method for preparing a metal ion-induced nanocluster membrane material of the present invention, by constructing a metal ion-monomer coordination cluster structure on the membrane surface, the structure uses defective pores formed by steric hindrance to increase the amount of transmission channels for permeating water and ions, thereby simultaneously improving the selective retention and permeation flux of the membrane material;

[0024] (2) The metal ion-induced nanocluster membrane material of the present invention has good interception effect on Congo red and inorganic salts, high water flux, and has broad application prospects in the field of zero discharge and resource recovery of high-salt wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a surface morphology image of the metal ion induced nanocluster membrane material of Example 5;

[0026] Figure 2 The particle size distribution diagram of the nanoclusters formed by aniline and pyrrole induced by metal ions in Example 1 and Example 2. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0028] The test methods for the performance indicators involved in the embodiments and comparative examples of the present invention are as follows:

[0029] Before testing, all membranes need to be filtered through pure water until the water flux stabilizes. The permeability of the membrane is recorded by measuring the amount of water collected under a transmembrane pressure of 0.4 to 1 bar. The dye retention performance of the membrane is evaluated by measuring the dye concentration before and after filtration by absorbance test. High-salt wastewater and high-salt organic wastewater tests are simulated by configuring salt solutions and dye / salt mixed solutions, and the change in salt concentration in the solution is measured by testing the conductivity of the solution. The separation performance of the composite membrane for dyes and dyes / salts is analyzed by cross-flow filtration. As a common form of filtration, cross-flow filtration uses pressure as the driving force to achieve the separation process. The following is the calculation formula for retention rate and water flux:

[0030] Retention rate R (%): calculated by the following formula:

[0031]

[0032] Wherein, C0 is the dye concentration before filtration, and C is the dye concentration before and after filtration;

[0033] Water flux J (L m-2h-1bar-1): calculated by the following formula:

[0034]

[0035] Where V is the volume of permeated water, A is the effective membrane area, ΔP is the transmembrane pressure, and Δt is the operating time.

[0036] The sources of information on some substances in this invention are as follows:

[0037] Polyvinylidene fluoride membrane (PVDF membrane): Manufacturer: Jinteng, membrane diameter is 50 mm, pore size is 0.22 μm.

[0038] Polytetrafluoroethylene membrane: Manufacturer: Jinteng, membrane diameter is 50 mm, pore size is 0.22 μm.

[0039] Pyrrole: Manufacturer: Aladdin, CAS No.: 109-97-7.

[0040] Aniline: Manufacturer: Aladdin, CAS No.: 62-53-3.

[0041] Dopamine hydrochloride: Manufacturer: Aladdin, CAS number: 62-31-7.

[0042] Cobalt nitrate hexahydrate: Manufacturer: Aladdin, CAS number: 10026-22-9.

[0043] Zinc chloride: Manufacturer: Aladdin, CAS number: 7646-85-7.

[0044] Copper nitrate trihydrate: Manufacturer: Aladdin, CAS number: 10031-43-3.

[0045] Sodium sulfate: Manufacturer: Aladdin, CAS number: 7757-82-6.

[0046] Congo Red: Manufacturer: Aladdin, CAS No.: 573-58-0.

[0047] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from the market or synthesized from raw materials purchased from the market.

[0048] Example 1

[0049] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0050] (1) Preparation of raw materials:

[0051] Polymer monomer: aniline;

[0052] Metal ion compounds: cobalt nitrate;

[0053] Polymer membrane: including effective area of ​​9.621cm 2 A polyvinylidene fluoride base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0054] (2) adding the polymer monomer, piperazine and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer, piperazine and the metal ion compound;

[0055] In a solution containing a polymer monomer, piperazine and a metal ion compound, the mass percentage concentration of the polymer monomer is 1.50%, the mass percentage concentration of piperazine is 0.175%, and the concentration of the metal ion is 0.01M;

[0056] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0057] (4) A 0.1% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 60° C. for 10 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0058] The final metal ion-induced nanocluster membrane material has a retention rate of 93.46% for 10 mg / L Congo red and 10.82% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 130.65 L m-2h-1bar. -1 .

[0059] like Figure 2 As shown, the particle size distribution diagram of aniline, piperazine and cobalt nitrate solution after mixing, the average particle size is 66.00nm.

[0060] Comparative Example 1

[0061] A method for preparing a metal ion-induced nanocluster membrane material is basically the same as that of Example 1, except that no metal ion compound is added in step (2).

[0062] The final metal ion-induced nanocluster membrane material has a retention rate of 91.68% for 10 mg / L Congo red and 89.38% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 16.94 L m-2h-1bar. -1 .

[0063] By comparing Comparative Example 1 with Example 1, it can be found that Comparative Example 1 has a large retention of Congo red and Na2SO4, but a very small water flux. This is because cobalt metal ions are added in Example 1, and under the coordination of metal ions, polymer monomers and piperazine form a cluster structure, and more defect structures are generated due to the steric hindrance effect during the polymerization of polyamide, and a relatively uniform regular morphology structure is formed on the surface. The change in the microstructure of the membrane surface greatly improves the selective separation of dyes and salts and the water flux.

[0064] Example 2

[0065] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0066] (1) Preparation of raw materials:

[0067] Polymer monomer: pyrrole;

[0068] Metal ion compounds: cobalt nitrate;

[0069] Polymer membrane: including effective area of ​​9.621cm 2 A polyvinylidene fluoride base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0070] (2) adding the polymer monomer, piperazine and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer, piperazine and the metal ion compound;

[0071] In the solution containing polymer monomer, piperazine and metal ion compound, the mass percentage concentration of polymer monomer is 0.15%, the mass percentage concentration of piperazine is 0.175%, and the concentration of metal ion is 0.05M;

[0072] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0073] (4) A 0.1% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 60° C. for 10 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0074] The final metal ion-induced nanocluster membrane material has a retention rate of 90.57% for 10 mg / L Congo red and 10.66% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 186.15 L m-2h-1bar. -1 .

[0075] like Figure 2 As shown, the particle size distribution diagram of pyrrole, piperazine and cobalt nitrate ion solution after mixing has an average particle size of 71.45 nm.

[0076] Comparative Example 2

[0077] A method for preparing a metal ion-induced nanocluster membrane material is basically the same as that of Example 2, except that no metal ion compound is added in step (2).

[0078] The final metal ion-induced nanocluster membrane material has a retention rate of 94.82% for 10 mg / L Congo red and 96.51% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 11.53 L m-2h-1bar. -1 .

[0079] By comparing Comparative Example 2 with Example 2, it can be found that Comparative Example 2 has a large retention of Congo red and Na2SO4, while the water flux is very small. This is because cobalt metal ions are added in Example 2. Under the coordination of metal ions, polymer monomers and piperazine form cluster structures, and more defect structures are generated due to the steric hindrance effect during the polymerization of polyamide. Moreover, a relatively uniform regular morphology structure is formed on the surface. The change in the microstructure of the membrane surface greatly improves the selective separation of dyes and salts and the water flux.

[0080] Example 3

[0081] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0082] (1) Preparation of raw materials:

[0083] Polymer monomer: dopamine hydrochloride;

[0084] Metal ion compounds: cobalt nitrate;

[0085] Polymer membrane: including effective area of ​​9.621cm 2 A polyvinylidene fluoride base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0086] (2) adding the polymer monomer and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer and the metal ion compound;

[0087] In the solution containing polymer monomers and metal ion compounds, the mass percentage concentration of the polymer monomers is 0.15%, and the concentration of the metal ions is 0.01M;

[0088] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0089] (4) A 0.1% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 60° C. for 10 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0090] The final metal ion-induced nanocluster membrane material has a retention rate of 94.46% for 10 mg / L Congo red and 8.37% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 432.81 L m-2h-1bar. -1 .

[0091] Example 4

[0092] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0093] (1) Preparation of raw materials:

[0094] Polymer monomer: aniline;

[0095] Metal ion compounds: cobalt nitrate;

[0096] Polymer membrane: including effective area of ​​9.621cm 2 A polyvinylidene fluoride base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0097] (2) adding the polymer monomer, piperazine and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer, piperazine and the metal ion compound;

[0098] In a solution containing a polymer monomer, piperazine and a metal ion compound, the mass percentage concentration of the polymer monomer is 0.15%, the mass percentage concentration of piperazine is 0.0875%, and the concentration of the metal ion is 0.025M;

[0099] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0100] (4) A 0.1% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 60° C. for 10 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0101] The final metal ion-induced nanocluster membrane material has a retention rate of 95.42% for 10 mg / L Congo red and 8.06% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 235.11 L m-2h-1bar. -1 .

[0102] Example 5

[0103] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0104] (1) Preparation of raw materials:

[0105] Polymer monomer: dopamine hydrochloride;

[0106] Metal ion compounds: cobalt nitrate;

[0107] Polymer membrane: including effective area of ​​9.621cm 2 A polyvinylidene fluoride base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0108] (2) adding the polymer monomer, piperazine and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer, piperazine and the metal ion compound;

[0109] In the solution containing polymer monomer, piperazine and metal ion compound, the mass percentage concentration of polymer monomer is 0.30%, the mass percentage concentration of piperazine is 0.175%, and the concentration of metal ion is 0.01M;

[0110] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0111] (4) A 0.1% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 60° C. for 10 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0112] The final metal ion-induced nanocluster membrane material has a retention rate of 93.46% for 10 mg / L Congo red and 9.81% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 102.55 L m-2h-1bar. -1 .

[0113] like Figure 1 As shown, the surface micromorphology of the membrane generated by interfacial polymerization under the action of metal ion cobalt presents a "peak-valley" structure with uniformly arranged clusters.

[0114] Example 6

[0115] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0116] (1) Preparation of raw materials:

[0117] Polymer monomer: pyrrole;

[0118] Metal ion compounds: zinc chloride;

[0119] Polymer membrane: including effective area of ​​9.621cm 2 A polyvinylidene fluoride base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0120] (2) adding the polymer monomer, piperazine and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer, piperazine and the metal ion compound;

[0121] In a solution containing a polymer monomer, piperazine and a metal ion compound, the mass percentage concentration of the polymer monomer is 0.05%, the mass percentage concentration of piperazine is 0.25%, and the concentration of the metal ion is 0.01M;

[0122] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0123] (4) A 0.05% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 50° C. for 20 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0124] The final metal ion-induced nanocluster membrane material has a retention rate of 98.64% for 10 mg / L Congo red and 10.82% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 113.96 L m-2h-1bar. -1 .

[0125] Example 7

[0126] A method for preparing a metal ion-induced nanocluster membrane material, the specific steps are as follows:

[0127] (1) Preparation of raw materials:

[0128] Polymer monomer: aniline;

[0129] Metal ion compounds: cobalt nitrate;

[0130] Polymer membrane: including effective area of ​​9.621cm 2 A polytetrafluoroethylene-based base membrane and a support membrane formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane; the amount of polypyrrole-coated bacterial cellulose used is 40 mg;

[0131] (2) adding the polymer monomer and the metal ion compound to a mixture of ethanol and water in a volume ratio of 2:5 to obtain a solution containing the polymer monomer, piperazine and the metal ion compound;

[0132] In a solution containing a polymer monomer, piperazine and a metal ion compound, the mass percentage concentration of the polymer monomer is 0.20%, the mass percentage concentration of piperazine is 0.0875%, and the concentration of the metal ion is 0.02M;

[0133] (3) pouring a solution containing polymer monomers and metal ion compounds onto one side of the polymer membrane, and after soaking for 10 minutes, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure;

[0134] (4) A 0.2% by weight 1,3,5-benzenetricarboxylic acid chloride n-hexane solution is poured onto the polymer film to deposit a metal ion-monomer coordination cluster structure on one side of the surface, and an interfacial polymerization reaction is performed. After the reaction, the material is thermally cured at 70° C. for 10 min and washed with water to obtain a metal ion-induced nanocluster film material.

[0135] The final metal ion-induced nanocluster membrane material has a retention rate of 95.34% for 10 mg / L Congo red and 4.01% for 0.5 g / L Na2SO4 aqueous solution at 25°C and 1 bar pressure, and a water flux of 496.31 L m-2h-1bar. -1 .

Claims

1. A method for preparing a metal ion-induced nanocluster membrane material, characterized in that: A solution containing polymer monomers and metal ion compounds is poured on one side of the polymer membrane, and after soaking, the solution is deposited on the polymer membrane to form a metal ion-monomer coordination cluster structure, and then a 1,3,5-benzenetricarboxylic acid chloride solution is poured on one side of the polymer membrane to deposit the metal ion-monomer coordination cluster structure, and an interfacial polymerization reaction is performed. After the reaction, the solution is thermally cured and washed with water to obtain a metal ion-induced nanocluster membrane material; The polymer monomer is a compound containing an amino group.

2. The method for preparing a metal ion-induced nanocluster membrane material according to claim 1, characterized in that: The polymer membrane comprises a base membrane and a support membrane. The support membrane is formed by vacuum filtering polypyrrole-coated bacterial cellulose onto the base membrane.

3. The method for preparing a metal ion-induced nanocluster membrane material according to claim 2, characterized in that: The basement membrane is a polytetrafluoroethylene filter membrane, an organic nylon filter membrane, a polypropylene filter membrane or a polyvinylidene fluoride filter membrane.

4. The method for preparing a metal ion-induced nanocluster membrane material according to claim 2, characterized in that: The effective area of ​​the basement membrane is 9.621 cm 2 The amount of polypyrrole-coated bacterial cellulose used is 20 to 60 mg.

5. The method for preparing a metal ion-induced nanocluster membrane material according to claim 1, characterized in that: The polymer monomer is aniline, pyrrole or dopamine, and the metal ion compound is cobalt nitrate, zinc nitrate, iron nitrate, copper nitrate, cobalt chloride, zinc chloride, iron chloride or copper chloride.

6. The method for preparing a metal ion-induced nanocluster membrane material according to claim 5, characterized in that: The solvent in the solution containing polymer monomers and metal ion compounds is a mixture of ethanol and water; in the solution containing polymer monomers and metal ion compounds, the mass percentage concentration of the polymer monomers is 0.05-1.50%, and the concentration of the metal ions is 0.025-0.2M.

7. The method for preparing a metal ion-induced nanocluster membrane material according to claim 6, characterized in that: The solution containing polymer monomers and metal ion compounds also contains piperazine, and the mass percentage concentration of piperazine does not exceed 0.50%.

8. The method for preparing a metal ion-induced nanocluster membrane material according to claim 1, characterized in that: The mass percentage concentration of the 1,3,5-benzenetricarboxylic acid chloride solution is 0.05-0.4%.

9. The method for preparing a metal ion-induced nanocluster membrane material according to claim 1, characterized in that: The thermal curing temperature is 50-70°C, and the thermal curing time is 10-20 minutes.

10. The metal ion-induced nanocluster membrane material prepared by the method according to any one of claims 1 to 9, characterized in that: The interception rate of the metal ion-induced nanocluster membrane material for Congo red is not less than 90.57%, the interception rate for inorganic salts is not higher than 10.82%, and the water flux is 102.55~496.31L m-2h-1bar -1 .

Citation Information

Patent Citations

  • Preparing method of zinc-coordination organic nano particle hybridization polyamide membrane

    CN109603563A

  • Preparation method, product and application of organic solvent nanofiltration membrane

    CN118403506A

  • Lithium ion selective permeable membrane as well as preparation method and application thereof

    CN119113829A

  • Heterophase synthesis of metal-coordinated framework materials for particle size control

    WO2013112823A1